From the Horse's Mouth: Economic Conditions and Investor Expectations of Risk and Return - Amromin, Gene; Sharpe, Steven A. (Management Science, 2014)
Data obtained from monthly Gallup/UBS surveys from 1998 to 2007 and from a special supplement to the Michigan Surveys of Consumer Attitudes and Behavior, run in 22 monthly surveys between 2000 and 2005, are used to analyze stock market beliefs and portfolio choices of household investors. We show that the key variables found to be positive predictors of actual stock returns in the asset-pricing literature are also highly correlated with investor's subjective expected returns, but with the opposite sign. Moreover, our analysis of the microdata indicates that subjective expectations of both risk and returns on stocks are strongly influenced by perceptions of economic conditions. In particular, when investors believe macroeconomic conditions are more expansionary, they tend to expect both higher returns and lower volatility. This is difficult to reconcile with the canonical view that expected returns on stocks rise during recessions to compensate household investors for increased exposure or sensitivity to macroeconomic risks. Finally, the relevance of these investors' subjective expectations is supported by the finding of a significant link between their expectations and portfolio choices. In particular, we show that portfolio equity positions tend to be higher for those respondents that anticipate higher expected returns or lower uncertainty. This paper was accepted by Brad Barber, finance.